Studying the nickel adsorption ability by nanosized Mn2O3/SiO2 material - Dai, Luu Minh; Thiem, Dao Ngoc; Thang, Pham Duc; Ninh, Vu The; Chuc, Pham Ngoc (Vietnam Journal of Chemistry, 2012)
The Mn2O3/SiO2 material containing nanosized Mn2O3 has been synthesized at low temperature (550oC) by the combustion method. Mn2O3/SiO2 characterization is examined by X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and BET (Brunaure-Emmet-Teller) measurements. The Mn2O3/SiO2 material is used for removing the nickel from wastewater. The nickel absorption capacities by the nanosized manganase oxide have calculated using Langmuir method.